Hermeneutics as innovative method to design the brand identity of a nanotechnology company. Issue 2 (4th September 2018) - Settembre-Blundo, Davide; Fernández del Hoyo, Alfonso Pedro; García-Muiña, Fernando Enrique
Abstract : Purpose: The purpose of this paper is to develop an innovative branding method based on the hermeneutical approach and interpretive theory, to respond to the need of a simple and effective tool to build corporate identity through an industrial brand identity design and, being a new business, has been considered the brand perception of their stakeholders as the main input to analyze. Design/methodology/approach: The case study of a small- and medium-sized enterprise (SME), that produces nanomaterials for the business-to-business (B2B) industrial market, is used to design the new hermeneutic branding method. The methodology process has been structured in four phases that have marked the investigation and that correspond to four different levels of knowledge that, in succession, between them, constituted the so-called hermeneutic circle. Findings: This new approach allowed us to understand the social phenomenon related to the brand: its characteristic, context and the brand itself. Though hermeneutic analysis has confirmed that business strategy is only part of a more complex system of brand management, it must also consider the competitive environment and the views of the stakeholders. Practical implications: This paper contributes to research on industrial branding by adopting the hermeneutical approach in managerial practice. This paper is the first of its kind in detail modelling the design phases of a B2B brand, providing an operational tool for marketing specialists. Originality/value: There is a lack of research studies in the methods for designing industrial brands. The contribution of this paper lies in proposing a new interpretative approach that, acknowledging the different expectations of the stakeholder in the supply chain, allows to draw a B2B brand that communicates the system values of the product and company.